Sentence repetition deficits in the logopenic variant of PPA: linguistic analysis of longitudinal and cross-sectional data. Issue 12 (2nd December 2018) - Hohlbaum, Kathrin; Dressel, Katharina; Lange, Inga; Wellner, Barbara; Etcheverry Sáez, Louise; Huber, Walter; Grande, Marion; Amunts, Katrin; Grodzinsky, Yosef; Heim, Stefan
ABSTRACT: Background : The logopenic variant of primary progressive aphasia (lvPPA) is the most recently identified subtype within the primary progressive aphasia spectrum. Data characterizing this subtype based on comprehensive testing and sophisticated error analyses over time are still rare. One of the two core features of this subtype is a deficit in sentence repetition. Aims : To provide a more fine-grained linguistic characterization of the sentence repetition deficit in lvPPA. Methods & Procedures : We longitudinally analyzed sentence repetition abilities of eight lvPPA patients (mean age 67.6 years; two women) and a group of seven healthy controls (mean age 66.7 years; three women) using a novel schema for the classification of linguistic errors. Outcomes & Results : At their first examination, patients with lvPPA showed an overall impaired repetition performance compared to controls with a variable degree of impairment on the first and all subsequent dates of measurement. Two patients presented with a steady, rather unimpaired profile, similar to the control group. In progression, however, five patients showed an increase of errors especially in the categories omissions and phonological errors, occasionally resulting in violation of syntactic rules. Conclusions : These results expand existing descriptions of repetition abilities in lvPPA patients. The paper thus provides a more fine-grained classification scheme for sentence repetition performance and emphasizes the role of omissions and phonological errors in lvPPA. This, in turn, offers new insights into the linguistic nature of sentence repetition deficits in lvPPA beyond the application of mere correctness judgments.